Small number enumeration processes of deaf or hard-of-hearing students: A study using eye tracking and artificial intelligence - Schindler, Maike; Doderer, Jan H.; Simon, Anna L.; Schaffernicht, Erik; Lilienthal, Achim J.; Schäfer, Karolin (Frontiers in Psychology, 2022)
Students who are deaf or hard of hearing (DHH) often show significant difficulties in mathematics learning. Previous studies have reported that students who are DHH lag several years behind in their mathematical development as compared to hearing students. As possible reasons, limited learning opportunities due to a lesser incidental exposure to numerical ideas, delays in language and speech development, and further idiosyncratic difficulties of students who are DHH are discussed; however, early mathematical skills and their role for mathematical difficulties of students who are DHH are not explored sufficiently. In this study, we investigate whether students who are DHH differ from hearing students in their ability to enumerate small sets (1–9)—an ability that is associated with mathematical difficulties and their emergence. Based on a study with N=63 DHH and N=164 hearing students from third to fifth grade attempting 36 tasks, we used eye tracking, the recording of students’ eye movements, to qualitatively investigate student enumeration processes. To reduce the effort of qualitative analysis of around 8,000 student enumeration processes (227 students x 36 tasks), we used Artificial Intelligence, in particular a clustering algorithm, to identify student enumeration processes from the heatmaps of student gaze distributions. Based on the clusterings, we found that gaze distributions of DHH and hearing students differed significantly on a group level, indicating differences in enumeration processes, with DHH students using advantageous processes (enumeration “at a glance”) more often than hearing students. The results indicate that students who are DHH do not lag behind in small number enumeration as compared to hearing students but, rather, appear to perform better than their hearing peers in small number enumeration processes—as well when conceptual knowledge about the part-whole relationship is involved. Our study suggests that the mathematical difficulties of students who are DHH are not related to difficulties in small number enumeration, which offers interesting perspectives for further research.